Land-use in the Electric Colombian System: Hidden Impacts and Risks of Large-scale Renewable Projects - Ramirez-Tovar, A.M.; Moreno-Chuquen, Ricardo; Moreno-Quintero, Renata (International Journal of Energy Economics and Policy, 2022)
In the sustainable development era, massive land-use for electricity production represents a crucial challenge for environmental and social systems. Available information about the use of land in this sector is limited, for that reason in this paper we include the power density methodology to evaluate land-use in Colombia to produce electricity. The power density metric depicts the relation between energy produced and area used in this process, considering extraction-conversion-storage. The analysis between power electricity generation and land-use is made for the Colombian electric system, finding that there is no direct relationship between the area occupied by a generation plant and the electricity produced, since the evidence does not show that at larger areas greater power is obtained. Hydropower plants have large spectrum values of power densities, depending on the dam construction purpose (river-flow control). Fossil-fired power plants require less land for its production even including the fuel extraction area. Photovoltaic and wind-power plants in this comparison have the lowest power density values, accordingly, they require far larger areas and represent a risk for sustainability in this perspective.